Appropriate seeding rate facilitates the simultaneous enhancement of population yield and lodging resistance in direct-seeded rice - Gai, Dongsheng; Wang, Yuxin; Li, Haipeng; Shi, Boting; Liu, Yong; Zhang, Qiang; Geng, Yanqiu; Ji, Dongming; Guo, Liying; Shao, Xiwen (Frontiers in Plant Science, 2025)
IntroductionDirect-seeded rice is characterized by simplicity, efficiency, and environmental friendliness, with its planting area progressively expanding. However, inappropriate seeding rates can result in issues such as lodging and reduced productive tillers, thereby constraining yield potential. Consequently, this study investigated the response mechanisms of tillering, the heterogeneity between main stems and tillers, and the susceptibility to lodging under varying seeding rates in direct-seeded rice. The aim was to identify an appropriate seeding rate that maximizes yield while mitigating lodging risks, thus providing a theoretical foundation for high-yield cultivation practices.MethodsUsing Jiyujing as the experimental material, a single-factor experimental design was employed, with seeding rates set at 45 kg ha-1 (S45), 75 kg ha-1 (S75), 105 kg ha-1 (S105), and 135 kg ha-1 (S135). ResultsResults indicated that the low seeding rate S45 enhanced tillering capacity and productive tillers but was constrained by an insufficient number of effective panicles, limiting overall yield. Conversely, the high seeding rate S135 increased the number of effective panicles but intensified intra-population competition, which hindered individual development, decreased spikelets per panicle, seed setting rate, thousand-grain weight, and lodging resistance, ultimately restricting yield. The intermediate seeding rate S105 achieved the highest yield by balancing population dynamics with individual growth and optimizing the synergy between effective panicle numbers and per-plant productivity. Furthermore, the high seeding rate S135 reduced the diameter, wall thickness, fullness, and physical-chemical component content of basal second internodes, elevating lodging risks. S135 also diminished the average diameter, volume, and surface area of the root system, exacerbating root lodging and yield losses.DiscussionTherefore, the seeding rate S105 represents the optimal choice for simultaneously enhancing high yield and lodging resistance in direct-seeded rice, offering a theoretical basis for rational plant density management in direct-seeded rice cultivation.